Nestedness and underlying processes of bird assemblages in Nanjing urban parks. Issue 4 (28th October 2020) - Tan, Xinwei; Yang, Xueru; Chen, Chuanwu; Wang, and Yanping
Abstract: Nestedness is an important pattern frequently reported for species assemblages on islands or fragmented systems. However, to date, there are few studies that comprehensively investigated faunal nestedness and underlying processes in urbanized landscapes. In this study, we examined the nestedness of bird assemblages and its underlying causal mechanisms in 37 urban parks in Nanjing, China. We used the line-transect method to survey birds from April 2019 to January 2020. We used the Weighted Nestedness metric based on Overlap and Decreasing Fill (WNODF) to estimate the nestedness of bird assemblages. We applied spearman partial correlation test to examine the relationships between nestedness ranks of sites and park characteristics (area, isolation, anthropogenic noise, number of habitat types, and building index), as well as between nestedness ranks of species and their ecological traits (body size, geographic range size, clutch size, minimum area requirement, dispersal ratio, and habitat specificity). We found that bird assemblages in urban parks were significantly nested. Park area, habitat diversity, building index, habitat specificity, and minimum area requirement of birds were significantly correlated with nestedness. Therefore, the nestedness of bird assemblages was caused by selective extinction, habitat nestedness, and urbanization. However, the nestedness of bird assemblages did not result from passive sampling, selective colonization, or human disturbance. Overall, to maximize the number of species preserved in our system, conservation priority should be given to parks with large area, rich habitat diversity, and less building index. From a species perspective, we should focus on species with large area requirement and high habitat specificity for their effective conservation.